Cultivation Intensity in Combination with Other Ecological Factors as Limiting Ones for the Abundance of Phytopathogenic Fungi on Wheat - Hýsek, Josef; Vavera, Radek; Růžek, Pavel (Microbial ecology, 2019)
In field and laboratory experiments during 2014-2017, we investigated the influence of lower and higher cultivation intensity of wheat and ecological factors (weather-temperature and rainfalls, year) on the occurrence of phytopathogenic fungi on the leaves of winter wheat. The prevailing fungi in those years were Mycosphaerella graminicola (Fuckel) J. Schrott and Pyrenophora tritici-repentis (Died.) Drechsler. Using cluster analysis, we statistically evaluated interrelationships of known factors on the abundance of the fungi on leaf surfaces. Our results showed strongest correlation with Mycosphaerella graminicola and Pyrenophora tritici-repentis abundance to be with lower cultivation intensity and year done by the temperature and the rainfalls. The two pathogens-Puccinia tritici Oerst and Hymenula cerealis Ellis & Everh. occurred only very sparsely in some years and had little positive or negative correlation with named factors. The semi-early and semi-late winter wheat varieties Matchball, Annie, Fakir, and Tobak were used for our experiments. Higher cultivation intensity had protective effect against leaf phytopathogenic fungi.
Keywords: Ecosystem; teplota; pšenice; Plant Diseases; Ascomycota; Temperature; Triticum; Basidiomycota; nemoci rostlin; ekosystém